Leadership, personality and digital skills and their relationship with productivity - Chávez - Plascencia, Iris Yoloxochilt Deyanira; Ávalos - Pelayo, Rafael (Universidad Francisco de Paula Santander, 2022)
The benefit derived from the culmination of the present research consists in the identification of leadership and personality factors that facilitate teachers to strengthen and/or acquire the digital competencies necessary for the implementation of hybrid teaching models, which are considered as the main decisive fact of the training process, not only at the undergraduate level, but also for other educational levels. It is important to note that this is a study in progress, therefore, it is a first approach, developed as a preliminary model, in which a relationship between the variables involved is proposed, determining from first impressions that the 4th industrial revolution has encouraged a rapid transformation of business models, where the skills of workers must be extended to cover digital areas.